Cargo and functional profile of saliva-derived exosomes reveal biomarkers specific for head and neck cancer - Hofmann, Linda; Medyany, Valentin; Ezić, Jasmin; Lotfi, Ramin; Niesler, Beate; Röth, Ralph; Engelhardt, Daphne; Laban, Simon Andreas; Schuler, Patrick; Hoffmann, Thomas K.; Brunner, Cornelia; Jackson, Edwin K.; et al. (Frontiers in medicine, 2022)
BackgroundExosomes contribute to immunosuppression in head and neck squamous cell carcinoma (HNSCC), a tumor entity which lacks specific tumor biomarkers. Plasma-derived exosomes from HNSCC patients correlate with clinical parameters and have potential as liquid biopsy. Here, we investigate the cargo and functional profile of saliva-derived exosomes from HNSCC patients and their potential as non-invasive biomarkers for disease detection and immunomodulation.MethodsExosomes were isolated from saliva of HNSCC patients (n = 21) and healthy donors (HD, n = 12) by differential ultracentrifugation. Surface values of immune checkpoints and tumor associated antigens on saliva-derived exosomes were analyzed by bead-based flow cytometry using CD63 capture. Upon co-incubation with saliva-derived exosomes, activity and proliferation of T cells were assessed by flow cytometry (CD69 expression, CFSE assay). Adenosine levels were measured by mass spectrometry after incubation of saliva-derived exosomes with exogenous ATP. miRNA profiling of saliva-derived exosomes was performed using the nCounter® SPRINT system.ResultsSaliva-derived, CD63-captured exosomes from HNSCC patients carried high amounts of CD44v3, PDL1 and CD39. Compared to plasma, saliva was rich in tumor-derived, CD44v3+ exosomes and poor in hematopoietic cell-derived, CD45+ exosomes. CD8+ T cell activity was attenuated by saliva-derived exosomes from HNSCC patients, while proliferation of CD4+ T cells was not affected. Further, saliva-derived exosomes produced high levels of immunosuppressive adenosine. 62 HD- and 31 HNSCC-exclusive miRNAs were identified. Samples were grouped in “Healthy” and “Cancer” based on their saliva-derived exosomal miRNA profile, which was further found to be involved in RAS/MAPK, NF-κB complex, Smad2/3, and IFN-α signaling.ConclusionsSaliva-derived exosomes from HNSCC patients were enriched in tumor-derived exosomes whose cargo and functional profile reflected an immunosuppressive TME. Surface values of CD44v3, PDL1 and CD39 on CD63-captured exosomes, adenosine production and the miRNA cargo of saliva-derived exosomes emerged as discriminators of disease and emphasized their potential as liquid biomarkers specific for HNSCC.